EFEKTIVITAS PENGGUNAAN VIDEO PEMBELAJARAN DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII D SEMESTER GENAP SMP XAVERIUS PRINGSEWU TAHUN PELAJARAN 2020/2021 - Pratiwi, Angelika Eka; Sutrisno AB, Joko (Lentera: Jurnal Ilmiah Kependidikan, 2021)
The problems in this study related to the low mathematical communication skills. The purpose of this study was to determine the effectiveness of the use of learning videos in improving mathematical communication skills of class VIII D students in the even semesters of Xaverius Pringsewu Junior High School. This research is a Classroom Action Research (CAR) with the subject of class VIII D students totaling 25 students. The increase in mathematical communication skills is seen from the test results at the end of each cycle. The test of mathematical communication ability has first been tested for validity and reliability and declared to be in compliance. The indicator of the success of CAR is if students mathematical communication skills classically reach the minimum category of being and experience an increase in each cycle. The results showed that there was an increase in students mathematical communication skills, from the first cycle the percentage of completeness 32% increased to 80% in the second cycle with the achievement of medium, high, and very high categories. This can also be seen from the achievement of the average value of the acquisition of students mathematical communication skills in the first cycle of 59,76 an increased to the second cycle of 74,96. The result of student learning activities also showed an increase, from the first cycle the percentage was 59,4% and increased to 81,25% in the second cycle. Thus, it can be concluded that “the use of learning videos is effective in improving the mathematical communication skills of class VIII D students in the even semester of Xaverius Pringsewu Junior High School for the 2020/2021 Academic Year”.